2012
DOI: 10.4152/pea.201202081
|View full text |Cite
|
Sign up to set email alerts
|

Na+Ion Conducting Hot-pressed Nano Composite Polymer Electrolytes

Abstract: Synthesis, characterization and polymeric battery studies of Na + ion conducting NanoComposite Polymer Electrolyte (NCPE) membranes: (1-x) [75PEO: 25NaPO 3 ]: x SiO 2 , where x = 0 -15 wt. (%), has been reported. NCPE membranes have been casted using a novel hot-press technique in place of the traditional solution cast method. The dispersal of SiO 2 in SPE host: (75PEO: 25NaPO 3 ), a conductivity enhancement of an order of magnitude achieved in NCPE film: [93 (75PEO: 25NaPO 3 ): 7 SiO 2 ]. This has been referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This indicates that the GPE is predominantly a good ionic conductor. Value of ionic transference number obtained in this study is nearly equal to the values reported by Chandra et al, and Kumar et al, for sodium ion conducting polymer electrolytes (Chandra et al, 2012;Kumar & Hashmi 2010). A resultant impedance plot of redox capacitor is shown in figure 07.…”
Section: Figure 03supporting
confidence: 76%
“…This indicates that the GPE is predominantly a good ionic conductor. Value of ionic transference number obtained in this study is nearly equal to the values reported by Chandra et al, and Kumar et al, for sodium ion conducting polymer electrolytes (Chandra et al, 2012;Kumar & Hashmi 2010). A resultant impedance plot of redox capacitor is shown in figure 07.…”
Section: Figure 03supporting
confidence: 76%
“…The dry powders of highest conducting composition were homogeneously mixed with different wt.% ratios of nano-fillers and heated ~ 70-80 o C to form a slurry, then pressed between SS blocks resulting finally into a mechanically stable CPEs. In the present research laboratory, a number of CPEs have been synthesized in this very quicker method [8][9][10].…”
Section: Hot-press Techniquementioning
confidence: 99%
“…Electrolytes of SIBs mainly include the following: liquid electrolytes (nonaqueous liquid electrolytes, aqueous liquid electrolytes, , ionic liquids, etc. ), glass and ceramic electrolytes, solid polymer electrolytes, gel polymer electrolytes, and so forth. In these electrolytes, nonaqueous liquid electrolytes have been widely investigated for SIB systems because of their wide electrochemical window, high ionic conductivity, low viscosity, and chemical and electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%